1977
DOI: 10.1073/pnas.74.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Transient accumulation of Okazaki fragments as a result of uracil incorporation into nascent DNA.

Abstract: Strains of Escherichia coli with a mutation in the sof(dnaS) locus show a higher than normal frequency of recombination (are hyper rec) and incorporate label into short (4-5S) DNA (Fig. 1). Second, an excision-repair system detects and removes uracil residues that may have escaped the action of dUTPase and were misincorporated into DNA. Lindahl (4) has described an N-glycosidase that catalyzes the cleavage of the uracildeoxyribose linkage in DNA, and nucleases, acting at the apyrinidinic acid site, might ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(146 citation statements)
references
References 13 publications
6
139
1
Order By: Relevance
“…Since extracts of ung dug strains lack detectable uracil-initiated BER [16], it would appear that Ung and Dug are the sole activities in E. coli capable of removing uracil from DNA. Thus, use of CY11 allows determination of the amount of uracil that escaped cleavage by dUTP pyrophosphatase and was incorporated into nascent DNA under various growth conditions [3]. We consistently observed that the level of uracil in DNA extracted from saturated cultures of CY11 was lower than that from early log cultures (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Since extracts of ung dug strains lack detectable uracil-initiated BER [16], it would appear that Ung and Dug are the sole activities in E. coli capable of removing uracil from DNA. Thus, use of CY11 allows determination of the amount of uracil that escaped cleavage by dUTP pyrophosphatase and was incorporated into nascent DNA under various growth conditions [3]. We consistently observed that the level of uracil in DNA extracted from saturated cultures of CY11 was lower than that from early log cultures (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Although the DNA polymerases of E. coli do not effectively discriminate dUTP from dTTP, little dUTP finds its way into E. coli DNA because of the action of dUTP pyrophosphatase, which hydrolyzes dUTP to dUMP and PP i [10]. In early studies of dut mutants, it was anticipated that the dut mutant DNA would contain uracil [10]; however, the nascent DNA of these mutants was found to be exceptionally fragmented [3]. Such fragmentation was consistent with the excision of transiently incorporated uracil by uracil-DNA glycosylase (Ung) and subsequent incision of the Ung-generated abasic sites by apurinic/apyrimidinic endonuclease [23].…”
Section: Uracil Accumulation In Cj236 (Dut-1 Ung-1) Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…The successive steps in the base excision repair pathway are thought to involve action of an AP endonuclease, DNA deoxyribophosphodiesterase, a DNA polymerase and a DNA ligase [1,2]. Uracil in DNA results from deamination of cytosine [3] or incorporation of dUMP instead of dTMP [4,5]. Deamination will result in a GC to AT transition mutation unless uracil is removed before the next round of replication.…”
Section: Introductionmentioning
confidence: 99%